Superação de dormência das sementes e controle químico de Momordicacharantia L. - Parreira, Mariana Casari [UNESP]; Cardozo, NilceuPiffer; Pereira, Fernada Campos Mastrotti [UNESP]; Alves, Pedro Luis da Costa Aguiar [UNESP] (My University, 2012)
This experiment were performed to evaluate methods of seeds scarification for overcoming dormancy and the efficacy of six herbicides registered for sugarcane to control adult plants of Mcharantia. The experimental design was completely randomized, with four replications in both trials. The first trial is a factorial 2x8 (two times of seeds collection (2006 and 2007) with eight methods of breaking dormancy (mechanical scarification; 100% and 50% concentrated sulfuric acid; 2% potassium nitrate for three and six hours; heat dried at 60°C; hot water at 60°C and an untreated control).In the second trial evaluated the control of M. charantia through six different herbicides: Imazapic, Metsulfuron-methyl, Metribuzin, 2,4-D, Amicarbazone, Paraquat and a control without herbicide application. Thus, it can be concluded that the seeds were immersed in concentrated sulfuric acid for three minutes and potassium nitrate for three hours gave a higher percentage and germination speed and the herbicide Metribuzin reached, albeit belatedly, a total control of M. charantia.
Overcoming dormancy seeds and chemical control of Momordicacharantia L.
Keywords: Bitter melon; Escarification; Herbicides